El «desaparecido» como sujeto político: una lectura desde Arendt - María José López Merino (Franciscanum, 2015)
Regimes of Terror, those that look for establishing a complete domination, not only systematically imprison and kill entire groups of people, but also seek to destroy the very notion of death as we know it. The «disappeared», present in different regimes of terror that took place throughout the twentieth century, is the concrete expression of this attempt. This is the thesis that I would like to argue in this article, following-sometimes closely sometimes not so closely-Hannah Arendt’s perspective. We want to look into the moral and political problem embodied by the figure of the «disappeared», focusing on how it took place in the Southern Cone dictatorships, especially in Chile under the military dictatorship of A. Pinochet.